Outing Africa - (:unkn) unknown (My University, 2021)
Contrary to anthropological discourse, which establishes exclusive links between homosexuality and initiation rites, and colonial discourse, which often documents unequal relationships between partners, present-day literature increasingly projects the Plutarchan charis or reciprocal obligingness. This chapter outlines developments regarding gender and sexuality in three stages. The first stage is from the mid-nineteenth century and the fin-de-siècle European sexual imaginary to the sexual initiation models of the 1970s in African countries as well as diasporic milieus, such as in France at a time when philosophy is imbued with Sartrean existentialism, and the United Kingdom with its first “Afro-Queer” protagonists. The second stage is from the late-twentieth-century narratives of sexual emancipation to the turn of the millennium to the contemporary moment culminating in transgenderism and the last stage include new vocabularies and new subjectivities created via the new media in the first two decades of the twenty-first century.
Keywords: African Research